Acute ischemic stroke : an evidence-based approach - Greer, David M., 1966- (Wiley-Liss, 2007)
"Acute Ischemic Stroke: An Evidence-based Approach provides readers with an overview of the clinical and biological evidence to support the current treatment of AIS and paves a road for discovery by highlighting the future directions of research. Laying out treatment plans and protocols in a handbook fashion designed for ease-of-use. Illustrated throughout with tables and figures, Acute Ischemic Stroke is a reference for the treatment of AIS for a range of healthcare professionals, including stroke neurologists, emergency room physicians, neurology residents and fellows, medical students, and nurse practitioners."--Jacket.